1988
DOI: 10.1021/ic00288a019
|View full text |Cite
|
Sign up to set email alerts
|

Structural studies of organomolybdenum complexes containing indium

Abstract: The reaction between InCl3 and 3 equiv of Na[Mo(CO)3(7j-C5H5)] affords the trimolybdenum-indium complex [In¡Mo(CO)3-( -05 5•))3] (2), the structure of which was established by X-ray crystallography. Compound 2 crystallizes in the monoclinic space group P2\/n with a = 11.463 (1) A,b = 17.854 (1) A, c = 13.572 (1) ,ß= 101.846 (8)°, and Z = 4. The structure comprises a central trigonal-planar indium atom bonded to three Mo(CO)3(t7-C5H5) fragments via In-Mo bonds. The corresponding reaction between InCl3 and 2 eq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

1991
1991
2004
2004

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 0 publications
2
13
0
Order By: Relevance
“…Smith et al have reported the reaction of GaMe 3 with CpW(CO) 3 H, which results in multiple activation of the Ga−C bonds to afford CpW(CO) 3 GaMe 2 , [CpW(CO) 3 ] 2 (μ 2 -GaMe), and [CpW(CO) 3 ] 3 (μ 3 -Ga) besides CH 4 . In the reaction of CpM(CO) 3 H (M = Mo, W) with InMe 3 , μ 3 -indium complexes [CpM(CO) 3 ] 3 (μ 3 -In) are produced exclusively . We also reported that irradiation of CpFe(CO) 2 SiMe 3 in the presence of RSiH 3 (R = t -Bu, CMe 2 CMe 2 H) gave silylene-bridged diiron complexes Cp 2 Fe 2 (CO) 3 (μ-SiHR) .…”
Section: Resultsmentioning
confidence: 99%
“…Smith et al have reported the reaction of GaMe 3 with CpW(CO) 3 H, which results in multiple activation of the Ga−C bonds to afford CpW(CO) 3 GaMe 2 , [CpW(CO) 3 ] 2 (μ 2 -GaMe), and [CpW(CO) 3 ] 3 (μ 3 -Ga) besides CH 4 . In the reaction of CpM(CO) 3 H (M = Mo, W) with InMe 3 , μ 3 -indium complexes [CpM(CO) 3 ] 3 (μ 3 -In) are produced exclusively . We also reported that irradiation of CpFe(CO) 2 SiMe 3 in the presence of RSiH 3 (R = t -Bu, CMe 2 CMe 2 H) gave silylene-bridged diiron complexes Cp 2 Fe 2 (CO) 3 (μ-SiHR) .…”
Section: Resultsmentioning
confidence: 99%
“…In ref. 2 we reported the reaction between InCl, and 2 equivalents of Na[M(CO),(q-C,H,)] (M = Mo or W) which afforded the anionic dichloro complexes [InCl, { M(CO),(q-C5Hs)}2]-(M = Mo, 1; or W, 2). Compound 1 was characterised by X-ray crystallography as [Na(thf),]-[InCI,{ Mo(CO),(q-C,H,)},] (hereafter la).…”
Section: Resultsmentioning
confidence: 99%
“…In ref. 2 we reported details of the reactions between InCl, and equivalent of either Na[ Mo(CO),(q-C5H ,)I or Na[ W(CO),( q-C5H5)] which afforded the anionic complexes [InCl,{ M- (q-C5H5))] can be made directly from the reaction between [MX(CO),(q-C5H5)] and InX. We carried out two similar reactions, viz.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Transition metal indium compounds have been studied in the past starting with W. Hieber's early work on In[Co(CO) 4 ] 3 in 1942 up to the present with N. C. Norman's contributions, namely, on group-6 indium complexes, e.g., [(η 5 -C 5 H 5 )(CO) 3 M] n InX 3 - n (L) (M = Cr, Mo, W; n = 2, 3; L = THF, py or other Lewis donors). Almost all known systems of the type (L m M) n InX 3 - n , which can be viewed as derivatives of trimethylindium or indiumtrihalides, exhibit carbonyl transition metal fragments. Rather few compounds exist which do not carry carbonyl ligands at the transition metal center, only two of which have been structurally characterized: mer -{[(CH 3 ) 3 P] 3 (H)(C 2 H 5 )Ir−In(C 2 H 5 ) 2 } and cis -{(Cy 2 PCH 2 CH 2 PCy 2 )[(CH 3 ) 3 SiCH 2 ]Pt−In[CH 2 Si(CH 3 ) 3 ] 2 } (Cy = cyclo-C 6 H 11 ) …”
Section: Introductionmentioning
confidence: 99%